Modulation of dendritic cell immune functions by plant components. Issue 2 (June 2016) - Aldahlawi, Alia M.
Abstract: Dendritic cells (DCs) are the key linkage between innate and adoptive immune response. DCs are classified as specialized antigen-presenting cells that initiate T-cell immune responses during infection and hypersensitivity, and maintain immune tolerance to self-antigens. Initiating T-cell immune responses may be beneficial in infectious diseases or cancer management, while, immunosuppressant or tolerogenic responses could be useful in controlling autoimmunity, allergy or inflammatory diseases. Several types of plant-derived components show promising properties in influencing DC functions. Various types of these components have been proven useful in clinical application and immune-based therapy. Therefore, focusing on the benefits of plant-based medicine regulating DC functions may be useful, low-cost, and accessible strategies for human health. This review illustrates recent studies, investigating the role of plant components in manipulating DC phenotype and function towards immunostimulating or immunosuppressing effects either in vitro or in vivo .